2017
DOI: 10.18203/2394-6040.ijcmph20172840
|View full text |Cite
|
Sign up to set email alerts
|

A demographic study on type of accidents, injuries and associated factors, patients attending emergency trauma care at tertiary care teaching hospital

Abstract: Background: Road traffic accidents (RTA) is considered to be among top five cause of concern in with morbidity and mortality with socioeconomic repercussions among developing countries. RTA’s are manmade disaster which involves human suffering and socioeconomic costs in terms of premature deaths, injuries, etc. The objective of study was to know the prevalence of various types of accidents, injuries and associated factors.Methods: This study is prospective observational study, was conducted at Tertiary Care Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Similar finding were observed by Pathak et al, (2020) 7 and Shaira et al, (2020) 12 in their study which quoted large majority of the subjects were males. Prasad et al, (2017) 13 also reported similar findings and it was stated that 135 (88.23%) victims were male and females were 18 (11.76%). Dutta et al, 14 stated that the males accounted for a majority (n=293, 83.5%) of the RTA victims and only 58 (16.5%) females were involved.…”
Section: Discussionmentioning
confidence: 57%
“…Similar finding were observed by Pathak et al, (2020) 7 and Shaira et al, (2020) 12 in their study which quoted large majority of the subjects were males. Prasad et al, (2017) 13 also reported similar findings and it was stated that 135 (88.23%) victims were male and females were 18 (11.76%). Dutta et al, 14 stated that the males accounted for a majority (n=293, 83.5%) of the RTA victims and only 58 (16.5%) females were involved.…”
Section: Discussionmentioning
confidence: 57%